Adsorption characteristics of ammonium exchange by zeolite and the optimal application in the tertiary treatment of coking wastewater using response surface methodology. - Zhao, Cui (Water Science and Technology)
Natural zeolite is a favorable NH4+-ion exchanger in the tertiary wastewater treatment. In this study, a natural Chinese zeolite was anatomized using the mercury injection method, X-ray diffraction, and scanning electron micrographs. The kinetic process of ammonium adsorption onto the zeolite was best described by the pseudo second order model; the adsorption equilibrium data fitted better to the Freundlich isotherm; and the exchange between ammonium and alkali/alkaline earth cations was in the order of Na+ > Ca2+ > K+ > Mg2+. Finally, the zeolite powder was applied for the tertiary treatment of coking wastewater, which still contained high concentration of ammonium after the secondary treatment by a sequencing batch reactor. The Box?Behnken design was used to design the experimental protocol, and the response surface methodology (RSM) was used for the optimization of adsorption factors. The RSM analysis showed the optimal adsorption factors as particle size, 0.03 mm; initial dosage of zeolite powder, 50.0 g/L; and contact time, 24 h. The highest ammonium removal rate was 75.0% predicted by the RMS. Considering settleability of the zeolite powder, the particle size of 0.25 mm was recommended in practice with a little loss of the ammonium removal: 70.9% as the RMS predicted.